Habitat use and movements of parrotfishes in a Hawaiian coral reef seascape - Annandale, Senifa F.; Turner, Jason P.; Lippi, Daniel L.; Dance, Michael; Wells, R. J. David; Rooker, Jay R. (Frontiers in Fish Science, 2024)
Parrotfishes (family Scaridae) are important to coral reef ecosystems and highly prized by both commercial and recreational fishers in the Hawaiian Islands. Although parrotfishes are known to be strictly diurnal, our knowledge of their habitat use and movement patterns across daily timescales in tropical systems is still somewhat limited. Here, acoustic telemetry was used to determine parrotfish habitat use and movements within a coral reef seascape at Puakō, Hawai'i. An array of acoustic receivers was deployed in a nearshore reef to track fine-scale movements of two common species: ember parrotfish (Scarus rubroviolaceus) and palenose parrotfish (S. psittacus). Transmitters were mounted externally on fish and tracked over a four-week period using an acoustic positioning system. Coral habitats (reef flat, fore reef) within the study area were mapped and used in conjunction with triangulated positions to characterize habitat use and movements. Findings indicated that both species commonly inhabited the fore reef habitat during the day (91.6% and 95.0% of total detections, respectively), spending limited time in the reef flat during the day and no time in this habitat at night. Activity spaces (based on 95% and 50% kernel utilization distributions) indicated that home ranges and core use of both species were significantly larger during the day than night, with daytime home ranges (mean ±1 SD) significantly greater for ember parrotfish (8712 ± 1991 m 2 ) than palenose parrotfish (3725 ± 1254 m 2 ). Hourly mean detections peaked during crepuscular periods for palenose parrotfish and to a lesser extent for ember parrotfish, which was linked to movements between shallower daytime (foraging) and nighttime (resting) areas. Kernel utilization distributions indicated that both species occupied similar core use areas of the seascape (overlap index > 0.5), with both intra-and interspecific overlapping distributions present. Finding from this study highlight the value of the fore reef habitat for both daytime foraging and nocturnal resting activities of ember parrotfish and palenose parrotfish. This study also affords valuable information on primary activity spaces of both species as well as overlap between these two common congeners, which is essential for developing management strategies to conserve parrotfish populations.